Potentially fatal new trend in performance enhancement: a cautionary note on nitrite - Petroczi, A.; Naughton, D. P. (Journal of the International Society of Sports Nutrition, 2010)
Background Considerable interest has been shown by athletes and scientists in the potential for nitric oxide and associated vasodilators to enhance performance. This study aims to explore potential misuse of vasodilators by the athletes, and to highlight the growing concern over these agents.